Analysis of The Influence of School Head Leadership on Teacher and Business Performance in SMP N 1 Baturraden Lesson Year 2018-2019 - Purwaningsih, Purwaningsih (International Conference of Moslem Society, 2019)
Improving the quality of education at school is not only the role of principal, but also the role of teacher and Administrative Staff (TU). The teacher works not only as a teacher but also an educator. Teachers must play an active role and place their position as professionals who work with high performance. Teacher and TU performance will be optimal, if integrated with good school principal and adequate work facilities. Effective headmaster leadership will be created if the principal has good character, behavior and skills.. This study aims to determine whether there is an influence of the principal's leadership with the performance of teachers and TU SMP N 1 Baturaden in Academic Year 2018/2019. The approach used in this study is a qualitative approach. The sample in this study are 39 teachers and 13 TU staffs. Methods of collecting data used in this study are observation, questionnaires and interviews.